Emergency hormonal contraception and body weight: analysis of data from the Health Survey for England, 2010. (13th November 2015) - Woodhall, Sarah C; Lowndes, Catherine M; Craig, Rachel; Mindell, Jennifer; Anderson, Jane; Guthrie, Kate; Johnson, Anne M; Nardone, Anthony
Abstract: Background: Emergency hormonal contraception (EHC) is available as levonorgestrel and ulipristal acetate. In 2013, evidence from clinical studies prompted a revision of product information to indicate reduced efficacy of one levenorgestral-containing EHC in women weighing more than 75 kg, and inefficacy in those weighing more than 80 kg. The European Medicines Agency subsequently reviewed evidence on EHC efficacy and concluded that available data were inconclusive. If future research were to substantiate an association between EHC efficacy and bodyweight, an understanding of the potential impact at a population level would be important. We used data from the Health Survey for England (HSE), 2010, to explore this potential impact. Methods: The Health Survey for England is an annually conducted nationally representative household survey of the general population resident in England. Information on participants' health and wellbeing and sociodemographic information are collected with face-to-face interviews, self-completed questionnaire booklets, and a nurse visit. In 2010, questions about sexual behaviour and contraceptive use, including EHC use in the 12 months preceding the interview, were included. Overall survey response among women was 63%. 92% completed the self-completion booklet, of whom 5% did not complete questions on contraception. We estimated EHC use in 1508 sexually experienced (reporting at least one sexual partner over the lifetime to the date of the interview) 16–44-year-old women stratified by bodyweight (measured as part of the nurse visit). Findings: 9% (95% CI 8–11) of sexually experienced 16–44-year-old women reported EHC use in the previous year. EHC use was reported more frequently among younger women (20% in 16–24 year olds, 8% in 25–34 year olds, and 3% in 35–44 year olds). Among women who reported EHC use in the previous year, 33% (95% CI 25–43) weighed more than 75 kg, and 67% (57–75) weighed 75 kg or less. 22% (15–31) weighed more than 80 kg, and 7% (6–9) weighed more than 95 kg. Interpretation: EHC could be ineffective in a substantial proportion of users if effectiveness were found to be lower among those with higher bodyweight. Young women would be particularly affected given the higher rates of EHC use in this group. However, larger proportions of older women, who use EHC less frequently, weigh over 75 kg. Existing guidance advises EHC use irrespective of body weight, and thus research is urgently needed to determine the association between body weight and EHC efficacy. Funding: The Health Survey for England was funded by the Health and Social Care Information Centre.